Optimization of a Rhodamine 6G-doped PMMA thin-slab laser - Tou, T.Y.; Yap, S.S.; Chin, O.H.; Ng, S.W. (ELSEVIER SCIENCE BV, 2007)
Poly(methyl methacrylate) (PMMA) and Rhodamine 6G (Rh6G) were first dissolved in chloroform, then dried and milled into powdery preform for fabrication into rectangular thin slabs (< 1 mm) by a hot-press molding technique. Aluminum was coated on two surfaces of dye-doped PMMA thin slabs as reflectors. Conversion efficiency, peak lasing wavelength and spectral bandwidth of dye laser emissions from these slabs, which were transversely pumped by a nitrogen laser, were measured as a function of the dye concentration, slab thickness, and aluminum coatings. Re-absorption of back-scattered fluorescence due to aluminum coating on the opposite surface increased the conversion efficiency from 10.5% to 15% while that on the back surface further increased it to 17.5%. The operation lifetime of 3000 pulses at 50% reduction in the dye laser output, as compared to earlier work on thicker slabs (5 mm), suggested that re-absorption of fluorescence did not cause significant photo-degradation of Rh6G. As the dye laser action was confirmed in a thin slab, the operation lifetime may represent a more realistic photostability of Rh6G in PMMA matrix. (c) 2006 Elsevier B.V. All rights reserved.